Attitude toward auditing, marketing and corporate governance (an examination based in Parsons' social action theory) - Gholamhossein Mahdavi; Abbas Ali Daryaei (International Journal of Corporate Social Responsibility (JCSR), 2016)
Auditing develops within a social context. On the basis of Parsons' social action theory, we examine whether auditors' attitude toward marketing activities influences the time balance between auditing and marketing activities and attitude toward the importance of corporate governance mechanisms. We use survey responses from 257 auditors in Iran. We conducted our analysis by applying a binary Probit regression and for additional analysis, we utilize neural networks. Attitude toward marketing has a positive significant relationship with balance time between auditing and marketing activities. And the attitude of auditors toward marketing has a positive significant relationship with attitude toward corporate governance. Also, the results showed a significant difference between industry expert auditors' attitude and other auditors toward marketing activities. Finally the results of this paper generally suggest that if artificial neural networks are employed in the prediction process, more reliable results will be achieved. The paper provides important insights into emerging issues and developments in auditing and marketing that have clear relevance to auditing research and practice. Drawing on our analytical framework, we provide directions for further opportunities for research of social theories and auditing.
Keywords: 650; Attitude; Auditing; Corporate Governance Mechanism; Marketing; Parsons' Social Action Theory